THE CONCEPT OF “FAMILY” IN PHRASEOLOGY - Shakirov, Bobur Mirzo Baxtiyar oʻgʻli; Shokirova, Nodira Murodjon qizi (Educational Research in Universal Sciences, 2023)
The article provides information about the concept of “family” in phraseology, the role of the family in society and the phraseological units used in relation to the family.